Assessment of the activities of European cultural heritage tourism sites during the COVID-19 pandemic - Mateusz Naramski; Adam R. Szromek; Krzysztof Herman; Grzegorz Polok (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The COVID-19 pandemic has had a significant impact on the way tourism activities are conducted. Restrictions on moving from place to place have likely limited the spread of the SARS-CoV-2 virus but have also led to economic crisis in many countries around the world. In this article, we assessed the impact of the COVID-19 crisis on the activities of cultural heritage tourism sites in Europe. Scientific research was carried out in industrial heritage tourism sites associated with the European Route of Industrial Heritage (ERIH). Analysis of the literature and the results of our own research indicated a strong impact of the pandemic on the examined sites, expressed in the limitation of the operating time of the sites, a decrease in the number of tourists attended to, and a decrease in revenues. No significant reduction in employment was noticed. These sites were not generally used in preventive actions during the health crisis. Only some managers took an active part in supporting emergency services in a difficult situation. We concluded that taking up innovative functions by tourism enterprises should be open innovation.
Keywords: 650; tourism; management; cultural heritage tourism; open innovation; ERIH; COVID-19pandemic; heritage tourism site; open innovation with digital transformation